(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the formation of Islamic historiography and analyzes its main genres, including siyar, maghazi, tarajim, and tabaqat. The study explores the semantic and terminological meanings of these genres and their development within the framework of Islamic sciences. Special attention is given to the early sources of Islamic history such as Ibn Ishaq’s Siyar, Ibn Hisham’s As-Siyra an-Nabawiyya, and al-Waqidi’s Kitab al-Maghazi. The role of hadith scholarship in shaping historical methodology and ensuring the reliability of historical reports is also discussed. The article highlights how Qur’anic narratives, hadith collections, and biographical literature contributed to the emergence of Islamic history as an independent scholarly discipline.